Birador - Vinarao, Edgardo; Star Cinema (Quezon City Star Cinema, 2001)
Birador is about a bad cop named Miked Santana who's a womanizer double crosser and murderer. As the movie unfolds, circumstances and fate conspire to transform Santana from scoundrel to human being.
VCD
Directed by Edgardo Vinarao.
Rudy Fernandez, Victor Neri, Daisy Reyes
Keywords: Action--Drama.; Feature films